2019
DOI: 10.1891/0886-6708.vv-d-18-00011
|View full text |Cite
|
Sign up to set email alerts
|

Hate the Players, or the Game? The Role of Court Mediators and Hearing Officers in the Civil Protection Order Process

Abstract: Civil Protection Orders (CPOs) are among the most common legal tools that victims of intimate partner violence and abuse (IPV/A) use to protect themselves. The current study adds to the CPO research by using quantitative data to look at how female survivors' experiences with court personnel (attorneys, mediators, and hearing officers) shape their satisfaction with the court process, and what types of individual and court-related factors are related to perceived fairness of court personnel. The current study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Turning back to the article I highlighted in the beginning of this essay, I want to outline one of the more important findings of our paper (and consequently the most important finding to myself as a court administrator). That being the finding that women in our sample were statistically significantly more likely to report higher levels of satisfaction with the overall court process when they also perceived the mediators and hearing officers as being fair to them (Carcirieri et al, 2019). Below, I show how we outlined our model when looking at our sample's satisfaction with the CPO court process (sentences not involving the mentioned finding have been removed to consolidate the section):…”
Section: Highlighting the Disconnect: Academic Results Sections/ Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Turning back to the article I highlighted in the beginning of this essay, I want to outline one of the more important findings of our paper (and consequently the most important finding to myself as a court administrator). That being the finding that women in our sample were statistically significantly more likely to report higher levels of satisfaction with the overall court process when they also perceived the mediators and hearing officers as being fair to them (Carcirieri et al, 2019). Below, I show how we outlined our model when looking at our sample's satisfaction with the CPO court process (sentences not involving the mentioned finding have been removed to consolidate the section):…”
Section: Highlighting the Disconnect: Academic Results Sections/ Datamentioning
confidence: 99%
“…One of the last articles I published as an academic (using the data collected from the court where I was employed) focused on Family Court mediators and hearing officers, and how they may influence domestic violence victims’ perceptions of fairness of the civil protection order (CPO) process (Carcirieri et al, 2019). Some of our findings were significant and suggested that negative behaviors committed by mediators and hearing officers influenced how women perceived the CPO process; therefore, the recommendations made were as follows: The findings indicate that interpersonal training for court staff should emphasize the importance of court personnel listening to and validating petitioners’ experiences with abuse, and to be more encouraging of victims’ right to seek protection in whatever form they feel is best, whether that be through a consent order or an appearance before a hearing officer .…”
Section: Highlighting the Disconnect: Academic Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations